2014
DOI: 10.1002/mnfr.201400396
|View full text |Cite
|
Sign up to set email alerts
|

Increased risk of insulin resistance in rat offsprings exposed prenatally to white rice

Abstract: White rice (WR) is a major staple food for people in developing countries and it may be responsible for the growing incidence of type 2 diabetes. Nonpregnant Female Sprague Dawley rats fed with WR or brown rice (BR) for 8 weeks were mated with age-matched male rats maintained on normal pellet over the same period. Offsprings were fed normal pellet after weaning until 8 weeks postdelivery. Rats fed with WR and their offsprings showed worsened oral glucose tolerance test, lower serum adiponectin levels, and high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 27 publications
2
11
0
Order By: Relevance
“…In this study, consumption of GBR and GABA produced significant changes that indicated a favorable priming of the gene of GBR and GABA in rat offspring with a tendency towards improved insulin sensitivity, suggesting that intrauterine exposure to GBR and GABA triggered changes that favored energy balance and body weight homeostasis [9], resulting in lower weight gain compared to that with an HFD. Moreover, a similar effect was observed in rat offspring that were exposed to brown rice during pregnancy and lactation [5], and since GBR has superior nutritional value, it was expected to produce similar outcomes.…”
Section: Discussionmentioning
confidence: 74%
See 3 more Smart Citations
“…In this study, consumption of GBR and GABA produced significant changes that indicated a favorable priming of the gene of GBR and GABA in rat offspring with a tendency towards improved insulin sensitivity, suggesting that intrauterine exposure to GBR and GABA triggered changes that favored energy balance and body weight homeostasis [9], resulting in lower weight gain compared to that with an HFD. Moreover, a similar effect was observed in rat offspring that were exposed to brown rice during pregnancy and lactation [5], and since GBR has superior nutritional value, it was expected to produce similar outcomes.…”
Section: Discussionmentioning
confidence: 74%
“…Moreover, we have demonstrated previously that white rice consumption by dams caused metabolic perturbations that were transmitted to the rat offspring [5]. In this study, consumption of GBR and GABA produced significant changes that indicated a favorable priming of the gene of GBR and GABA in rat offspring with a tendency towards improved insulin sensitivity, suggesting that intrauterine exposure to GBR and GABA triggered changes that favored energy balance and body weight homeostasis [9], resulting in lower weight gain compared to that with an HFD.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Hypomethylation of the adipose tissue promoters of Tlr1, Tlr2, and linker for activation of T cells Mice Embryonic Cited2 deletion + Maternal high fat diet [197] Increased penetrance of cited2-induced defects including cardiac malformation, adrenal agenesis, and other defects Decreased expression (mRNA) of Pitx2c in Cited2-deficient embryos Macaque Maternal high fat diet [190,191,193] Increased hepatic Npas2 expression (mRNA) [226] Worsened glucose tolerance…”
Section: Hypomethylation Of the Pancreatic Il13ra2 Genementioning
confidence: 99%